DETERMINING AND VERIFYING THE GEOMETRIC CHARACTERISTICS OF HELICAL GROOVES IN THE WORM IN PLANETARY TOROIDAL DRIVES IN A MORE EFFECTIVE WAY - Jarmila VOJTKOVÁ (Scientific Journal of Silesian University of Technology. Series Transport, 2017)
In the toroidal drive, a screw-shaped groove is cut into the globoid worm. There is contact with the rolling element in this groove. This helix can be described by parametric equations. When calculating the values of the first and second curvature of the curve, as well as the radius of curvature, we must calculate the individual derivations. A new, more effective way is to determine the values already mentioned by using NX software only. When using Siemens PLM NX software, it is not necessary to determine individual derivations and their values, although the NX software determines the radii of the first and second curvature, based on the defined helix curve.